Pinoy in da dyipni Filipino values as reflected in the jeepney - Aguda, Denjo A.; Talaga, Lovely Liezle DG. (2008)
The study uncovered the Filipino values reflected and manifested in the behavior and experience of people in the Pinoy jeepney. it basically concentrated in the Baguio- Camp 6 route which is a 20 to 30 minutes ride from the city. It follows a postmodern ethnography approach in which the researchers have the freedom of writing the structure into the way they wanted to. Observations are done inside the jeepney and drivers and passengers of Baguio-camp 6 route are interviewed to validate those observations. This output is a presentation of the several experiences of selected informants with the Pinoy jeepney. Voices of the informants are heard. The output is resented in a narrative manner taking into details the shared experiences among the informants and between the researchers.Certain values and behaviors are identified while the use of native Tagalog and some Ilocano terms are taken into consideration to grasp the truest sense of the words. This study is helpful in the field of academe and also for future purposes to further understand Filipino values and behavior. As the researchers interact within the people of the community, certain ethical consideration and methods were followed to avoid mistakes that would lead to the disturbance of the fieldwork. The researchers are not detached from the experiences of the informants. The scope of the study is concerned particularly within the community of Camp 6. The researchers looked at the manifestations of three umbrella concepts associated in Filipino values. These are as follows: the concepts of reciprocity, the concept of hiya and the concept of personal space. But as the method of grounded theorizing suggest, the other narrated experiences and observations in the jeepney that are not necessarily connected with the three concepts are given equal regards as well. Researchers findings indicate that people show or manifest these values in different ways. The main reason is that people are brought up in different environments, sees the world in different perspective and treasures different values. And passengers have several experiences surrounding their rides in the jeepneys. What we need to understand is that camp 6 is populated by different ethnoliguistic groups. And passengers have different ethnicity backgrounds. This is a fragmentary presentation of the experienced and readily observed behavior and also the narrated experiences of passengers and the researchers as well -- Author's Abstract.
Thesis (Bachelor of Arts) -- University of the Philippines Baguio, 2008.
Includes bibliographical references (leaves 85-86)
Keywords: Social values -- Philippines -- Baguio City; Filipinos -- Social life and customs; Values -- Philippines -- Baguio City